2020
DOI: 10.1080/09500693.2019.1710782
|View full text |Cite
|
Sign up to set email alerts
|

Curious children and knowledgeable adults – early childhood student-teachers’ species identification skills and their views on the importance of species knowledge

Abstract: To cite this article: Tuula H. Skarstein & Frode Skarstein (2020) Curious children and knowledgeable adults-early childhood student-teachers' species identification skills and their views on the importance of species knowledge,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 28 publications
(34 reference statements)
4
33
0
6
Order By: Relevance
“…As children's questions may be expressions of an interest of a certain subject, one could assume that experiencing nature elements would elicit questions from the children. This assumption is in line with schoolteachers' (Mygind et al, 2019) and early childhood student-teachers' (Skarstein & Skarstein, 2020) experiences in outdoor settings. However, Fischer and Madsen (2002) observed that preschool children exploring material in or from a natural outdoor environment (e.g.…”
Section: Introductionsupporting
confidence: 61%
“…As children's questions may be expressions of an interest of a certain subject, one could assume that experiencing nature elements would elicit questions from the children. This assumption is in line with schoolteachers' (Mygind et al, 2019) and early childhood student-teachers' (Skarstein & Skarstein, 2020) experiences in outdoor settings. However, Fischer and Madsen (2002) observed that preschool children exploring material in or from a natural outdoor environment (e.g.…”
Section: Introductionsupporting
confidence: 61%
“…In the preface of the book Ecological literacy: Educating our children for a sustainable world [86], Fritjof Capra writes: "Education for sustainable living fosters both an intellectual understanding of ecology and emotional bonds with nature that make it more likely that our children will grow into responsible citizens who truly care about sustaining life." [86] (xv) Play and exploration in natural environments (including wild spaces, urban green spaces and gardens) are considered by many researchers to be an important means for fostering both early understanding of ecology and emotional bonds to nature [87][88][89][90][91]. This view is based on studies that illustrate how children's play in nature provides them with opportunities to become familiar with the natural world through direct experiences and thus enables them to build personal and meaningful relationships with nature [87][88][89].…”
Section: Outdoor Play and Learningmentioning
confidence: 99%
“…Chawla and Rivkin [89] argue that exploring nature together, sharing emotions and paying attention to living organisms and their way of life, develops the perspective-taking which is important for developing sympathy for other living things. Skarstein and Skarstein [91] also point out the role of adults in providing children with opportunities to learn about local nature by sharing their knowledge of common plants and animals encountered while jointly exploring nature. In their study, they discuss how knowledge of local nature is an important factor in developing a desire for environmental protection.…”
Section: Outdoor Play and Learningmentioning
confidence: 99%
“…Giving children the possibility to experience nature may also encourage their appreciation of nature (Chawla 2007;Chawla and Rivkin 2014). Several researchers consider children's play in natural environments as an essential element in early childhood (EC) sustainability education, since it provides children with opportunities to build personal and meaningful relationships with nature and to strengthen their environmental consciousness (Barratt, Barratt-Hacking, and Black 2014;Chawla and Rivkin 2014;Skarstein and Skarstein 2020). Beery and Jørgensen (2018) also argue for the importance of childhood nature experiences as a point of departure for the development of ecological ideas and embodied environmental understanding.…”
Section: Introductionmentioning
confidence: 99%